Exploring mathematics teachers’ insights and practices of project-based learning in primary schools of Nyamasheke district, Rwanda - Ukobizaba, Fidele; Maniraho, Jean Francois; Uworwabayeho, Alphonse (Frontiers in Education, 2025)
IntroductionProject-based Learning (PjBL) holds a paramount foundation in fostering a human resource equipped with practical skills and innovative mindset necessary for sustainable growth and prosperity.MethodsThis study investigated the teachers’ insights and practices in project-based learning teaching methods of mathematics, with eight teachers selected in one district of Rwanda. A qualitative exploratory design was used to collect data from eight teachers selected through convenience sampling. In-depth interviews were conducted, and the data were thematically analyzed using Taguette software.ResultsThe results from the study showed that teachers have a limited understanding of PjBL, which hinders its application in their regular mathematics instruction. Lack of awareness, time constraints, limited skills, overcrowded classes, lack of school leaders’ support, and lack of interest are barriers to teachers incorporating PjBL in mathematics instructions.DiscussionMathematics teachers’ understanding and classroom practices of project-based learning influence its implementation. This study contributes to the growing body of knowledge on project-based learning by providing empirical insights into how mathematics teachers in primary schools of Nyamasheke district, Rwanda, perceive and apply PjBL within their instructional practices.